Evaluating high power laser therapy (HPLT) as treatment for chemotherapy‐induced oral mucositis in paediatric patients with oncohematological diseases. Issue 3 (10th March 2023) - Ludovichetti, Francesco Saverio; Costa, Giorgia; Signoriello, Anna Giulia; Stellini, Edoardo; Zerman, Nicoletta; Biffi, Alessandra; Mazzoleni, Sergio
Abstract: Background: Oral mucositis (OM) is one of the most debilitating side effects of chemotherapy. Among the current methods used in OM management, the feasibility of high power laser therapy (HPLT) has been proposed but not fully evaluated. Aim: The aim of this study was to evaluate the efficacy of HPLT in the treatment of OM in paediatric patients. Design: Fourteen oncohematological paediatric patients treated with chemotherapy and/or hematopoietic stem cell transplantation and affected by OM at different grades were enrolled in this study. All patients were treated with a class IV laser device in four sessions for four consecutive days, OM was evaluated with the WHO‐OTS scale. The perception of pain was assessed by the visual analog scale. Photographs of and information about lesions and patient questionnaires were taken and collected, respectively. Descriptive analyses and the Wilcoxon signed‐rank test (nonparametric test) were used, with a statistical significance of α = .05. Results: After a week into the treatment, 57% of patients were completely healed, whereas the whole cohort experienced a drastic decrease in pain, from an average value of 5.8–1.1 ( p = .0016). The average number of injuries per patient decreased from 7.4 to 3.1 ( p = .008). Conclusion: High power laser therapy appears to be a safe and efficacious method for managing OM. It reduces pain and severity of oral cavity injuries. Further studies are needed to determine the optimal parameters useful in OM treatment and to evaluate the relative effectiveness of HPLT to other treatments like LLLT.